2019
DOI: 10.1134/s1022795419040094
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nuclear Microsatellite Markers with Long (Tri-, Tetra-, Penta-, and Hexanucleotide) Motifs for Three Larch Species Based on the de novo Whole Genome Sequencing of Siberian Larch (Larix sibirica Ledeb.)

Abstract: Siberian larch (Larix sibirica Ledeb.) is one of the major boreal tree species in Eurasia and has a considerable economic and ecological value. Despite that importance, the development and use of microsatellite markers in this species remain limited. Microsatellite markers are considered to be a valuable tool for estimation of population diversity and structure. Availability of a draft reference assembly of the Siberian larch genome allowed us to identify 1015 microsatellite loci or simple sequence repeats (SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Thanks to whole genome or partial genome sequencing of conifers, it became possible to develop easily genotyped species-specific microsatellite markers for various conifer species, for example, for such main species of the Eurasian boreal forests as Pinus sibirica Du Tour (Belokon et al, 2016) and Larix sibirica Ledeb. (Oreshkova et al, 2017(Oreshkova et al, , 2019. These markers facilitate population genetic studies, identification of the timber and plant material origin in the fight against illegal logging and control over the legal origin of plant material, effective reforestation, identification of clone material, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to whole genome or partial genome sequencing of conifers, it became possible to develop easily genotyped species-specific microsatellite markers for various conifer species, for example, for such main species of the Eurasian boreal forests as Pinus sibirica Du Tour (Belokon et al, 2016) and Larix sibirica Ledeb. (Oreshkova et al, 2017(Oreshkova et al, , 2019. These markers facilitate population genetic studies, identification of the timber and plant material origin in the fight against illegal logging and control over the legal origin of plant material, effective reforestation, identification of clone material, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Its ecological and economical importance has stimulated exploration of its population structure [ 25 , 26 , 27 ] and the development of early genetic markers [ 28 , 29 ]. The whole-genome sequencing made possible the development of additional highly informative species-specific SSR markers in L. sibirica [ 30 , 31 ], which can be used in different practical applications, including tracking the timber origin to fight illegal logging [ 32 ]. The release of the first nuclear [ 21 ], chloroplast [ 33 ] and mitochondrial [ 34 ] genome assemblies for Siberian larch, and recently for Japanese larch [ 22 ], has contributed to the development of the genomic resource for the larch genus.…”
Section: Introductionmentioning
confidence: 99%
“…These repeating units can be located sequentially one after another forming tandem repeats. This class of repeats forms simple structures such as microsatellite or simple sequence repeat loci, widely used as genetic markers [15], including in Siberian larch [16,17]. Another broad class represents interspersed repeats, which are more complex in structure and practically do not form blocks that follow each other.…”
Section: Introductionmentioning
confidence: 99%
“…Their longevity and resistance to harsh conditions contribute to their dominance in different ecosystems of the Northern Hemisphere. Conifer genomes have remarkable gigantic sizes (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), which is not associated with genome-wide duplication or polyploidization events, at least recent ones [1]. It was suggested that the main cause of the increased sizes is the propagation of repetitive DNA sequences [2].…”
Section: Introductionmentioning
confidence: 99%